Ultra-wideband elliptical patch antenna for microwave imaging of wood. Issue 9 (27th May 2019) - Saeidi, Tale; Ismail, Idris; Wen, Wong Peng; Alhawari, Adam R. H.
Abstract: This paper presents the design of an elliptical shape ultra-wide band antenna for imaging of wood. The antenna is constructed comprising an elliptical shape of patch loaded by a stub to resonate at lower bands, strip loading at the back, and chamfered ground. Despite having miniaturized dimensions of 20 mm × 20 mm, the proposed antenna shows better results compared to recent studies. The simulation results depict a good ultra-wide bandwidth from 2.68 to 16 GHz, and 18.2–20 GHz. Besides, the proposed antenna has two low-frequency bands at 0.89–0.92 and 1.52–1.62 GHz, maximum gain of 5.48 dB, and maximum directivity of 6.9 dBi. The measurement outcomes are performed in air, plywood, and high-density wood and show a good agreement with the simulated results done using electromagnetic simulator CST. In addition to that, the measurement results of S-parameters, transmitted and received signals show a good agreement with the simulated results. Besides, the measured results illustrate a good isolation and uniform illumination among arrays as well as the received signals' shapes do not change in different environments, but only the amplitude. Hence, the proposed antenna seems to be adequate for microwave imaging of wood.